A comparative analysis of nutrient utilisation and meat quality parameters of boer goats and South African mutton merinos - Sheridan, Rouxlene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2001.